Aplikasi Peregangan Otot untuk Mengurangi Keluhan Nyeri Otot Rangka (Musculoskeletal Disorders) pada Sopir Trans Jogja - Andiansi Rahmawati; Agus Suwarni; Yamtana Yamtana (Poltekkes Kemenkes Yogyakarta, 2018)
Health problem and occupational disease is often found, because relationship between diseaseand occupation is often unable to be detected. One type of health problems and occupational disease is musculoskeletal disorders. One high risk occupation to musculoskeletal disorders isbus driver. This study, conduct an effort to reduce musculokeletal disorders among TransJogjabus drivers by implementing muscle streching.This study was a quasi experiment with non equivalent control group design, and held on Mei 2018 with.The number of drivers sample was 30.The study results show that the decrease average of musculoskeletal disorders in the controlgroup is 16,44 %, while in the experiment group it is 79,17 %. Statistical analysis using MannWhitney test at ?=0,05 proves that the difference is significant (p-value ? 0,001). Therefore, itcan be concluded that muscle stretching can reduce musculoskeletal disorders among TransJogja bus drivers.